Antibacterial corrosion-resistant coating and preparation method thereof
The antibacterial and corrosion-resistant coating prepared by combining nano-silver ion-loaded mesoporous silica nanoparticles and zinc powder corrosion inhibitor solves the problems of existing coatings in terms of short-lasting antibacterial effect and insufficient corrosion resistance, and achieves comprehensive performance improvement and enhanced stability of the coating.
Patent Information
- Application Number
- CN202511137453.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-14
- Publication Date
- 2025-10-10
AI Technical Summary
Existing metal surface protective coatings have short-lasting antibacterial effects, insufficient corrosion resistance, and unsatisfactory overall performance. In addition, the preparation process is complex and it is difficult to meet the high-performance requirements of modern industry.
A composite system of nanosilver ion-loaded mesoporous silica nanoparticles as an antibacterial additive, zinc powder-containing corrosion inhibitor, nano-montmorillonite, modified epoxy resin and polyurethane prepolymer is used. Nanoparticles are synthesized by the soft template method, zinc powder, modified epoxy resin and polyurethane prepolymer are dispersed by high-speed stirring, and the proportion of each component is precisely controlled to prepare an antibacterial and corrosion-resistant coating.
The coating's antibacterial, corrosion-resistant and comprehensive performance are significantly improved, providing reliable biological protection and stability, solving the shortcomings of existing technologies, and the coating exhibits excellent protective effects in complex environments.
Smart Images

Figure CN120758125A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of coating materials, and in particular to an antibacterial and corrosion-resistant coating and a preparation method thereof. Background Art
[0002] In the prior art, protective coatings for metal surfaces are typically based on a variety of materials, such as epoxy resins and polyurethanes. These coatings improve the metal's corrosion resistance and antibacterial properties to a certain extent. For example, some coatings use composite formulas containing specific ratios of epoxy resins, polyurethanes, and other fillers and additives in order to achieve better overall performance. However, these coatings often have some shortcomings, such as insufficiently long-lasting antibacterial effects, corrosion resistance that needs to be improved, or the coating's overall properties, such as flexibility and adhesion, that fail to meet practical application requirements.
[0003] The main technical challenges of protective coatings for metal surfaces are: on the one hand, the coatings must possess excellent antimicrobial properties to prevent microbial growth on the metal surface, leading to biocorrosion; on the other hand, the coatings must provide reliable corrosion protection while also maintaining excellent adhesion, flexibility, and weather resistance. Inadequate performance in these areas can lead to cracking and detachment during use, reducing the protective effect. Furthermore, existing coatings often struggle to simultaneously meet these complex performance requirements, especially under varying environmental conditions. Summary of the Invention
[0004] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide an antibacterial and corrosion-resistant coating and a preparation method thereof to solve one or more problems in the prior art.
[0005] To achieve the above object, the technical solution of the present invention is as follows: An antibacterial and corrosion-resistant coating, comprising, by mass percentage: Nanosilver ion loaded mesoporous silica nanoparticles antibacterial additive 2%-5%; Contains 5%-10% zinc powder corrosion inhibitor; Nano-montmorillonite 3%-8%; Modified epoxy resin 30%-40%, Polyurethane prepolymer 20%-30%; Other additives.
[0006] Furthermore, the preparation method of the nano silver ion loaded mesoporous silica nanoparticle antibacterial adjuvant is: Synthesis of mesoporous silica nanoparticles by soft template method; Dispersing mesoporous silica nanoparticles in a silver nitrate solution, and performing an ion exchange reaction at a temperature of 20°C to 40°C and a pH value of 8-10 for 2h to 6h; The nano-silver ion-loaded mesoporous silica nanoparticle antibacterial adjuvant is obtained by washing and drying.
[0007] Furthermore, the zinc powder is mixed with an organic solvent and a dispersant, dispersed by high-speed stirring, and then ball-milled to uniformly disperse the zinc powder particles in the organic medium, wherein the particle size of the zinc powder is 0.1 μm-1 μm.
[0008] Furthermore, the epoxy resin is modified with a silane coupling agent, the mass ratio of the silane coupling agent to the epoxy resin is 1:10-1:20, and the reaction is carried out at a temperature of 60° C.-80° C. for 2 h-4 h.
[0009] Furthermore, the polyurethane prepolymer is prepared by reacting polyether polyol, isocyanate and chain extender, wherein the molar ratio of polyether polyol to isocyanate is 1:1.5-1:2.5, and the molar ratio of chain extender to isocyanate is 0.5:1-1:1.
[0010] Furthermore, the other additives include, by mass percentage, 20%-30% deionized water, 1%-3% emulsifier, 0.5%-2% dispersant, 0.2%-1% leveling agent, and 3%-8% curing agent.
[0011] In order to make the technical effect complete, the second set of technical solutions of the present invention is a preparation method, which complements and nests with the first set of solutions and includes the following steps: Premixing stage: under nitrogen protection atmosphere, deionized water, emulsifier and dispersant are added to the reaction vessel and mixed evenly, and then nano-silver ion-loaded mesoporous silica nanoparticle antibacterial additive, zinc powder-containing corrosion inhibitor, nano-montmorillonite, modified epoxy resin and polyurethane prepolymer are added in sequence, with a stirring speed of 300r / min-600r / min and a stirring time of 1h-3h; Grinding and refining stage: transfer the premixed slurry to a sand mill, add grinding media, and grind to a particle size of 0.1μm-1μm for 0.5h-2h; Initiation of polymerization: transfer the ground slurry back to the reaction vessel, heat it to 60-70°C, add the curing agent, stir at a speed of 200-400 r / min, and react for 2-4 hours; Post-processing stage: The paint after the reaction is filtered and de-bubbled to obtain an antibacterial and corrosion-resistant coating.
[0012] Specifically, the grinding medium is zirconia beads with a diameter of 0.5 mm to 2 mm.
[0013] Preferably, the coating material prepared by the preparation method is applied to a metal surface.
[0014] Compared with the prior art, the beneficial technical effects of the present invention are as follows: (1) Improved antibacterial performance This solution significantly improves antimicrobial performance by combining a silver nanoparticle-loaded mesoporous silica nanoparticle antimicrobial additive with a zinc powder-containing corrosion inhibitor. The silver nanoparticle-loaded mesoporous silica nanoparticle antimicrobial additive continuously releases silver ions, exerting a long-lasting antimicrobial effect, while the zinc powder corrosion inhibitor acts as a sacrificial anode to protect the metal surface and prevent microbial growth. This combination not only enhances the antimicrobial effect but also extends the antimicrobial life of the coating, effectively resolving the issue of short-lived antimicrobial effects in existing technologies and providing more reliable biological protection for metal surfaces.
[0015] (2) Enhanced corrosion resistance This solution significantly enhances the coating's corrosion resistance by combining the shielding and isolation properties of nano-montmorillonite with the sacrificial anodic protection provided by a zinc-containing corrosion inhibitor. The nano-montmorillonite's layered structure effectively blocks the penetration of corrosive media, while the zinc-containing corrosion inhibitor forms a protective film on the metal surface through an electrochemical reaction. These two mechanisms work synergistically to protect the metal from corrosion at both physical and chemical levels. This combined effect ensures the coating exhibits excellent corrosion resistance in complex environments, significantly surpassing existing single-protection strategies.
[0016] (III) Optimization of comprehensive performance This solution optimizes the overall performance of the coating by creating a composite system of modified epoxy resin and polyurethane prepolymer. The modified epoxy resin provides excellent adhesion and chemical resistance, while the polyurethane prepolymer imparts good flexibility and weather resistance. This composite system not only improves the mechanical properties of the coating but also enhances its stability under various environmental conditions. Furthermore, by precisely controlling the ratio of each component, the coating achieves a balanced balance between antibacterial, corrosion-resistant, and comprehensive performance, resolving the problem of suboptimal overall performance in existing coatings.
[0017] (IV) Improvement of coating stability and construction performance This solution significantly improves the coating's stability and application performance by optimizing the types and proportions of other additives, such as deionized water, emulsifiers, dispersants, leveling agents, and curing agents. Deionized water, used as a dispersion medium, reduces the coating's VOC content, complying with environmental protection requirements. Emulsifiers and dispersants ensure uniform dispersion of the various ingredients, preventing sedimentation and agglomeration. The leveling agent improves the coating's surface smoothness and reduces the potential for microbial attachment. This optimized additive system ensures excellent leveling and uniformity during application, further enhancing the coating's protective effectiveness and service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1It is a flow chart of the steps of the preparation method of the present invention. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and exemplary explanations. It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not intended to limit the conditions for the implementation of the present invention. Therefore, they have no technical significance. Any modification of the structure, change in the proportion relationship or adjustment of the size should still fall within the scope of the technical content disclosed in the present invention without affecting the efficacy and purpose of the present invention.
[0020] Application Overview In the field of metal surface protection, the industry generally adopts a variety of methods to solve the problems of metal antibacterial and corrosion resistance. A common method is to use traditional organic antimicrobial agents. Although these antimicrobial agents can inhibit the growth of microorganisms to a certain extent, they often have problems such as short-term antibacterial effects and easy development of drug resistance. Especially in complex use environments, their antibacterial properties will decline rapidly. In addition, traditional corrosion-resistant coatings mostly rely on a single protection mechanism, such as simple chemical film formation or physical shielding. These methods are often difficult to provide long-term and effective protection when facing complex corrosive environments. They are prone to cracking and shedding of the coating, causing the metal substrate to be exposed to the corrosive medium.
[0021] To enhance the overall performance of coatings, some improvement proposals attempt to improve the coating's adhesion, flexibility, and weather resistance by adding various additives or employing composite materials. However, these improvements often have limitations. For example, certain additives may react adversely with other components in the coating, affecting the overall performance of the coating; or, while improving one property, other important properties, such as the balance between flexibility and adhesion, may be sacrificed. Furthermore, the existing coating preparation process is relatively complex, and the application process may involve operational difficulties and high costs, limiting its widespread adoption in practical applications.
[0022] In summary, although the existing technology has made certain progress in solving the problems of antibacterial and corrosion resistance of metal surfaces, it still has defects such as short-lasting antibacterial effect, insufficient corrosion resistance, unsatisfactory comprehensive performance and complex preparation process, which makes it difficult to meet the demand of modern industry for high-performance metal protective coatings.
[0023] The specific technical solutions are as follows 1. Preparation of antibacterial additives The preparation of nano-silver ion loaded mesoporous silica nanoparticle antibacterial adjuvant is as follows: Mesoporous silica nanoparticles are synthesized using the soft template method. The specific steps are: first, dissolve an appropriate amount of a soft template agent (such as pluronic P123) in water, then add a silicon source (such as ethyl orthosilicate). The reaction is then allowed to react at a specific temperature to form silica nanoparticles with a mesoporous structure. The reaction temperature is typically 35°C-45°C, and the reaction time is 24-48 hours.
[0024] The synthesized mesoporous silica nanoparticles are dispersed in a silver nitrate solution and subjected to an ion exchange reaction for 2 to 6 hours at a temperature of 20°C to 40°C and a pH of 8 to 10. The pH of the solution can be controlled by adjusting the amount of ammonia added.
[0025] After the reaction, the silver ion-loaded mesoporous silica nanoparticles were collected by centrifugation and washed several times with deionized water to remove impurities such as unreacted silver nitrate.
[0026] The washed nanoparticles are placed in a vacuum drying oven and dried at 60° C.-80° C. for 12 h-24 h to obtain nano-silver ion loaded mesoporous silica nanoparticle antibacterial adjuvant.
[0027] 2. Preparation of corrosion inhibitor The preparation of the corrosion inhibitor containing zinc powder is as follows: Weigh appropriate amounts of zinc powder (particle size 0.1 μm-1 μm), organic solvent (such as ethanol) and dispersant (such as polyethylene glycol).
[0028] Mix the zinc powder with the organic solvent and the dispersant, and stir and disperse them in a high-speed stirrer at a speed of 800 r / min-1200 r / min for 30 min-60 min.
[0029] The stirred mixture is transferred to a ball mill, and grinding media (such as zirconia beads) are added. The mixture is ball-milled and dispersed for 2-4 hours to uniformly disperse the zinc powder particles in the organic medium to obtain a zinc powder-containing corrosion inhibitor.
[0030] 3. Preparation of modified epoxy resin The preparation of modified epoxy resin is as follows: Weigh appropriate amounts of epoxy resin (such as bisphenol A epoxy resin) and silane coupling agent (such as KH-550).
[0031] Mix the silane coupling agent and epoxy resin in a mass ratio of 1:10-1:20 and react at a temperature of 60-80°C for 2-4 hours. Stir continuously during the reaction to allow the silane coupling agent to react evenly with the epoxy groups in the epoxy resin molecular chain.
[0032] After the reaction is completed, the modified epoxy resin is cooled to room temperature and set aside.
[0033] IV. Preparation of polyurethane prepolymer The polyurethane prepolymer is prepared as follows: An appropriate amount of polyether polyol (such as polypropylene glycol), isocyanate (such as toluene diisocyanate), and chain extender (such as ethylene glycol) are weighed.
[0034] The polyether polyol and isocyanate are mixed in a molar ratio of 1:1.5-1:2.5 under a nitrogen atmosphere, and reacted at a temperature of 60-80°C for 2-3h.
[0035] The chain extender is added in a molar ratio of 0.5:1-1:1 with respect to the isocyanate, and the reaction is continued at a temperature of 60-80°C for 1-2h to obtain the polyurethane prepolymer.
[0036] V. Preparation of other additives The other additives include deionized water, emulsifier (such as polyoxyethylene octyl phenyl ether), dispersant (such as polycarboxylate), leveling agent (such as polyacrylate), and curing agent (such as modified amine curing agent). These additives are commercially available and can be used directly.
[0037] VI. Preparation of coating The preparation process of the coating is as follows: (I) Pre-mixing stage Under a nitrogen atmosphere, deionized water, emulsifier, and dispersant are added to the reaction vessel, and the stirring device is turned on to stir at a speed of 300-600r / min for 5-10min to ensure that the system is fully mixed and uniform. Then, the nano-silver ion loaded mesoporous silica nanoparticle antibacterial additive, the inhibitor containing zinc powder, the nano-montmorillonite, the modified epoxy resin, and the polyurethane prepolymer are sequentially added, and the stirring is continued at a speed of 300-600r / min for 1-3h to ensure that the components are uniformly dispersed in the system and a stable pre-mixed slurry is formed.
[0038] (II) Grinding and refining stage The pre-mixed slurry is transferred to a sand mill, and zirconium oxide beads with a diameter of 0.5-2mm are added as grinding media. The slurry is ground to a particle size of 0.1-1μm. The rotation speed of the sand mill is controlled at 1000-2000r / min during the grinding process, and the grinding time is 0.5-2h. The addition amount of the grinding media and the grinding time are adjusted to ensure that the particle size of the slurry meets the requirements.
[0039] (III) Initiation of polymerization stage The slurry after being finely ground is transferred back to the reaction container, and is heated to 60-70 DEG C, and a curing agent is added, and the reaction is stirred at a speed of 200-400 r / min for 2-4 h. During the reaction, the temperature and stirring speed are controlled to ensure that the curing reaction is fully carried out.
[0040] (Four) post-treatment stage The coating after the reaction is filtered, and a filter with a filtering precision of 5-10 um is used to remove impurities and large particles in the coating. Then the filtered coating is placed in a vacuum degassing machine, and is degassed at a vacuum degree of -0.09 MPa to -0.1 MPa for 10-20 min to remove bubbles in the coating, so that the antibacterial and corrosion-resistant coating is obtained.
[0041] Seven, application of the coating The antibacterial and corrosion-resistant coating of the present application can be applied to the surface of metal by spraying, brushing or dipping, etc. When spraying, air spraying or airless spraying equipment can be used, and the spraying pressure is controlled to be 0.2-0.5 MPa, and the spraying distance is 15-30 cm. When brushing, a brush is used to dip the coating and evenly apply it on the surface of the metal. When dipping, the metal part is immersed in the coating, and the residence time is determined according to the thickness requirement of the coating, and is generally 1-5 min. After the coating is applied, it is dried at room temperature for 24-48 h, or is baked and dried at 60-80 DEG C for 1-2 h, so that a protective coating with excellent antibacterial and corrosion-resistant properties is formed.
[0042] To prove the effectiveness of the technical scheme in the present application, the performance of the coating material is also tested, and the experimental scheme is as follows: Experimental purpose The present experiment aims to verify the influence of the ratio of the nano-silver ion loaded mesoporous silica nanoparticle antibacterial aid (antibacterial aid), zinc powder containing corrosion inhibitor (corrosion inhibitor) and nano-montmorillonite (montmorillonite) in the claim on the performance of the antibacterial and corrosion-resistant coating, and to explore the relationship between each variable and the performance of the coating.
[0043] Variable and range of experimental group Antibacterial aid: 2-5%; Corrosion inhibitor: 5-10%; Montmorillonite: 3-8%.
[0044] The variable values of the control group are not in the range of the experimental group.
[0045] Experimental grouping Ten experimental groups are designed, including a blank control group, four control groups and five parameter groups. The variables of each group are shown in the following table.
[0046] Table 1 of the experimental group formula ratio:
[0047] Experimental procedures Prepare materials according to the proportion of each experimental group, and the proportions of other ingredients are fixed.
[0048] According to the preparation process, pre-mixing, grinding and refining, initiating polymerization and post-treatment are carried out in sequence to prepare the coating.
[0049] The prepared coating was evenly coated on the surface of a metal specimen of the same size and material, with a coating area of 10 cm×10 cm and a coating thickness of 0.1 mm.
[0050] After the coating is completely cured, the performance test of the coated specimens is carried out.
[0051] Performance Testing Adhesion test: GB / T 9286-1998 "Paint and varnish adhesion test by cross-cut method" is used to test the adhesion of the coating to the metal substrate. The results are expressed in grades (0-5). The smaller the grade, the better the adhesion.
[0052] Corrosion resistance test: The specimens were immersed in a 3.5% NaCl solution for 72 hours, the corrosion conditions were observed, and the corrosion rate (mm / a) was calculated.
[0053] Antibacterial performance test: Refer to GB / T 31456-2015 "Antibacterial Coatings" to test the antibacterial rate (%) of the coating against Escherichia coli.
[0054] Table 2: Material proportion and performance of the experimental group:
[0055] Weighted scoring mechanism In order to make the experimental results intuitive and quantifiable, this scheme introduces a simple weighted scoring mechanism.
[0056] The weights of adhesion, corrosion resistance, and antibacterial performance are set at 30%, 40%, and 30%, respectively. The calculation formula is as follows: Weighted score = (Adhesion weight × Adhesion score + Corrosion resistance weight × Corrosion resistance score + Antibacterial weight × Antibacterial score) Adhesion level, corrosion rate, and antibacterial rate were normalized to a scale of 0-100, and then a comprehensive score was calculated based on the weights. The normalization formula is: Normalized score = (actual value - minimum value) / (maximum value - minimum value) × 100.
[0057] Below is a table of test records including weighted scores.
[0058] Table 3: Material proportions and properties of the experimental group
[0059] Data Analysis Blank control group (experimental group 1): The performance was poor, indicating that the existing technology was insufficient in terms of antibacterial and corrosion resistance.
[0060] Control group (experimental groups 2-5): Some performance has been improved, but the overall performance is still inferior to the parameter group, indicating that the effect is not ideal when the variable ratio is outside the scope of the claims.
[0061] Parameter groups (experimental groups 6-10): Performance was superior to the control group across the board, demonstrating that the variable ranges defined in the claims have significant technical effects. Experimental group 8 received the highest weighted score (85.67), validating the rationality and practical significance of the variable ranges defined in the parameter group.
[0062] Analyze the performance trend of parameter groups based on principles The weighted score increased from Group 6 to Group 7, indicating improved coating performance. At the molecular level, the increased proportion of antimicrobial additives released more silver ions, enhancing the antimicrobial effect. The increased proportions of corrosion inhibitor and montmorillonite enhanced the sacrificial anode protection and coating density, respectively. The synergistic effect of these three factors improved the overall coating performance.
[0063] The weighted scores continued to rise from Group 7 to Group 8, reaching a peak in Group 8. Increasing the proportion of antimicrobial additives and corrosion inhibitors further enhanced the antimicrobial and corrosion resistance. Increasing the proportion of montmorillonite further improved the coating's density, optimized its structure, and enabled more uniform release of silver and zinc ions, improving the coating's overall performance.
[0064] The weighted score decreased from Group 8 to Group 9. Increasing the proportion of antimicrobial additives may lead to excessive silver ion concentration, resulting in toxicity, or induce structural changes within the coating, affecting performance. Increasing the proportion of montmorillonite may affect the coating's rheological properties and reduce adhesion, indicating complex interactions between the components.
[0065] The weighted scores continued to decline from Group 9 to Group 10. Increasing the corrosion inhibitor content may introduce impurities, affecting the coating structure and reducing adhesion and corrosion resistance. Increasing the montmorillonite content further affects the coating's rheological properties, reducing its ability to spread and adhere to the metal surface.
[0066] Example Example 1
[0067] A method for preparing an antibacterial and corrosion-resistant coating comprises the following steps: Preparation of antibacterial additives containing nanosilver ions loaded with mesoporous silica nanoparticles: Mesoporous silica nanoparticles were synthesized using the soft template method: 3.0 g of Pluronic P123 (soft template agent) was dissolved in 100 mL of deionized water, and 12.6 g of tetraethyl orthosilicate (TEOS) was added under stirring and reacted at 40°C for 24 h.
[0068] The synthesized mesoporous silica nanoparticles (2.0 g) were dispersed in 100 mL of silver nitrate solution (0.1 mol / L) and an ion exchange reaction was carried out for 4 h at 30°C and pH 9. The pH of the solution was controlled by adjusting the amount of ammonia added.
[0069] After the reaction, the silver ion-loaded mesoporous silica nanoparticles were collected by centrifugation and washed three times with deionized water to remove impurities such as unreacted silver nitrate.
[0070] The washed nanoparticles were placed in a vacuum drying oven and dried at 70°C for 12 h to obtain nanosilver ion-loaded mesoporous silica nanoparticle antibacterial adjuvant.
[0071] Preparation of zinc powder corrosion inhibitor: Weigh 4.0 g of zinc powder (particle size 0.5 μm), 8.0 g of ethanol, and 0.4 g of polyethylene glycol.
[0072] Zinc powder was mixed with ethanol and polyethylene glycol, and stirred and dispersed in a high-speed mixer at a speed of 1000 r / min for 40 min.
[0073] The stirred mixture was transferred to a ball mill, zirconia beads were added, and ball milling was performed for 3 h to uniformly disperse the zinc powder particles in the organic medium to obtain a zinc powder-containing corrosion inhibitor.
[0074] Preparation of modified epoxy resin: Weigh 100 g of bisphenol A epoxy resin and 10 g of silane coupling agent KH-550.
[0075] Silane coupling agent KH-550 and epoxy resin were mixed in a mass ratio of 1:10 and reacted at 70°C for 3 hours. Stirring was performed continuously during the reaction to ensure that the silane coupling agent reacted evenly with the epoxy groups in the epoxy resin molecular chain.
[0076] After the reaction is completed, the modified epoxy resin is cooled to room temperature and set aside.
[0077] Preparation of polyurethane prepolymer: Weigh 40 g of polypropylene glycol (molecular weight 1000), 32 g of toluene diisocyanate, and 8 g of ethylene glycol.
[0078] Under a nitrogen atmosphere, polypropylene glycol and toluene diisocyanate were mixed in a molar ratio of 1:2 and reacted at 70°C for 2.5 h.
[0079] Ethylene glycol was added with a molar ratio of ethylene glycol to toluene diisocyanate of 0.8:1, and the reaction was continued at 70° C. for 1.5 h to obtain a polyurethane prepolymer.
[0080] Preparation of other additives: Deionized water: 250 g Emulsifier (polyoxyethylene octylphenyl ether): 8 g Dispersant (polycarboxylate): 4 g Leveling agent (polyacrylate): 1.5 g Curing agent (modified amine curing agent): 25 g Preparation of coating: Pre-mixing stage: Under a nitrogen atmosphere, 250 g of deionized water, 8 g of emulsifier, and 4 g of dispersant were added to the reaction vessel, the stirring device was turned on, and the mixture was stirred at a speed of 400 r / min for 8 min to ensure that the system was fully mixed.
[0081] 2.5 g of nanosilver ion-loaded mesoporous silica nanoparticle antibacterial additive, 6.0 g of zinc powder-containing corrosion inhibitor, 4.0 g of nano-montmorillonite, 35 g of modified epoxy resin and 25 g of polyurethane prepolymer were added in sequence, and stirring was continued at 400 r / min for 2 h to ensure that all components were evenly dispersed in the system to form a stable premixed slurry.
[0082] Grinding and refining stage: The premixed slurry was transferred to a sand mill and ground to a particle size of 0.5 μm using 1.0 mm diameter zirconium oxide beads as the grinding medium. The sand mill speed was controlled at 1500 r / min for 1.5 h.
[0083] By adjusting the amount of grinding media added and the grinding time, ensure that the particle size of the slurry meets the requirements.
[0084] Initiation of polymerization stage: Transfer the ground slurry back to the reaction vessel, heat it to 65°C, add 25 g of curing agent, and stir at 300 r / min for 3 h. During the reaction, pay attention to controlling the temperature and stirring speed to ensure that the curing reaction proceeds fully.
[0085] Post-processing stage: The paint after the reaction was filtered, and impurities and large particles in the paint were removed using a filter with a filtration accuracy of 7 μm.
[0086] Then the filtered paint is placed in a vacuum defoaming machine, and defoamed for 15 min under the condition of vacuum degree of-0.095 MPa, to remove the bubbles in the paint, to obtain the antibacterial corrosion-resistant coating.
[0087] Examples two to ten The environment parameters and constants of this example are the same as those of example one, except that the proportion values of the variable nano-silver ion loaded mesoporous silica nanoparticle antibacterial additive, zinc powder containing corrosion inhibitor, and nano-montmorillonite are respectively: Example two: 2.5%, 6%, 4%; Example three: 3%, 7%, 5%; Example four: 3.5%, 8%, 6%; Example five: 4%, 9%, 7%; Example six: 4.5%, 10%, 8%; Example seven: 5.0%, 5.0%, 3.0%; Example eight: 4.0%, 7.0%, 5.0%; Example nine: 3.0%, 8.0%, 6.0%; Example ten: 3.5%, 6.0%, 4.0%.
[0088] The technical features described in the above examples can be combined in any way. In order to make the description concise, not all possible combinations of the technical features described in the above examples are described, however, as long as the combinations of the technical features do not contradict each other, they should be considered as the scope of the present disclosure.
Claims
1. An antibacterial and corrosion-resistant coating, characterized in that: Calculated by mass percentage, including: Nanosilver ion loaded mesoporous silica nanoparticles antibacterial additive 2%-5%; Contains 5%-10% zinc powder corrosion inhibitor; Nano-montmorillonite 3%-8%; Modified epoxy resin 30%-40%, Polyurethane prepolymer 20%-30%; Other additives.
2. The antibacterial and corrosion-resistant coating according to claim 1, characterized in that: The preparation method of the nano silver ion loaded mesoporous silica nanoparticle antibacterial adjuvant is: Synthesis of mesoporous silica nanoparticles by soft template method; Dispersing mesoporous silica nanoparticles in a silver nitrate solution, and performing an ion exchange reaction at a temperature of 20°C to 40°C and a pH value of 8-10 for 2h to 6h; The nano-silver ion-loaded mesoporous silica nanoparticle antibacterial adjuvant is obtained by washing and drying.
3. The antibacterial and corrosion-resistant coating according to claim 1, characterized in that: The preparation method of the zinc powder-containing corrosion inhibitor is: Zinc powder is mixed with an organic solvent and a dispersant, dispersed by high-speed stirring, and then ball-milled to disperse the zinc powder particles uniformly in the organic medium, wherein the particle size of the zinc powder is 0.1 μm-1 μm.
4. The antibacterial and corrosion-resistant coating according to claim 1, characterized in that: The preparation method of the modified epoxy resin is: The epoxy resin is modified with a silane coupling agent, the mass ratio of the silane coupling agent to the epoxy resin is 1:10-1:20, and the reaction is carried out at a temperature of 60° C.-80° C. for 2 h-4 h.
5. The antibacterial and corrosion-resistant coating according to claim 1, characterized in that: The polyurethane prepolymer is prepared by reacting polyether polyol, isocyanate and chain extender, wherein the molar ratio of polyether polyol to isocyanate is 1:1.5-1:2.5, and the molar ratio of chain extender to isocyanate is 0.5:1-1:
1.
6. The antibacterial and corrosion-resistant coating according to claim 1, wherein: The other additives include, by mass percentage, 20%-30% deionized water, 1%-3% emulsifier, 0.5%-2% dispersant, 0.2%-1% leveling agent, and 3%-8% curing agent.
7. A preparation method based on the antibacterial and corrosion-resistant coating according to claims 1-6, characterized in that The following steps are involved: Premixing stage: under nitrogen protection atmosphere, deionized water, emulsifier and dispersant are added to the reaction vessel and mixed evenly, and then nano-silver ion-loaded mesoporous silica nanoparticle antibacterial additive, zinc powder-containing corrosion inhibitor, nano-montmorillonite, modified epoxy resin and polyurethane prepolymer are added in sequence, with a stirring speed of 300r / min-600r / min and a stirring time of 1h-3h; Grinding and refining stage: transfer the premixed slurry to a sand mill, add grinding media, and grind to a particle size of 0.1μm-1μm for 0.5h-2h; Initiation of polymerization: transfer the ground slurry back to the reaction vessel, heat it to 60-70°C, add the curing agent, stir at a speed of 200-400 r / min, and react for 2-4 hours; Post-processing stage: The paint after the reaction is filtered and de-bubbled to obtain an antibacterial and corrosion-resistant coating.
8. A preparation method according to claim 7, characterized in that: The grinding medium is zirconia beads with a diameter of 0.5 mm to 2 mm.
9. A preparation method according to claim 7, characterized in that: The coating material prepared by the preparation method is applied to metal surfaces.
Citation Information
Cited By
Anti-corrosion coating containing lanthanum cerium oxide and preparation method of anti-corrosion coating
CN121203515A
Anticorrosive coating containing lanthanum cerium oxide and preparation method thereof
CN121203515B
Long-acting antibacterial mildew-proof coating as well as preparation method and application thereof
CN121673951A